A comparison of microCT and microPET for evaluating lymph node metastasis in a rat model - Flechsig, Paul; Kratochwil, Clemens; Warth, Arne; Rath, Daniel; Eichwald, Viktoria; Huber, Peter E.; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Giesel, Frederik L. (Molecular imaging & biology, 2016)
PurposeThe demand to optimize multidisciplinary treatment strategies in patients with benign and malignant diseases of the lung and other organs has led to the increased need of mechanistic proof-of-concept studies in preclinical small animal models using new non-invasive imaging methods. Therefore, we evaluated the role of microPET and microCT for mediastinal lymph node staging in an orthotopic lung cancer model in rats.ProceduresHuman lung cancer cells (NCI-H460) were injected transthoracically in nude rats (NIH-RNU). After 2 weeks of tumour growth, animals underwent multiphase contrast-enhanced microCT using ExiTron nano 12000 as a contrast agent and dynamic microPET using the tracer 2-deoxy-2-[18F]fluoro-d-glucose ([18F]FDG). Thereafter, animals were sacrificed for histological analysis.ResultsLate phase micro X-ray computed tomography (microCT) revealed the best delineation of lymph node metastases, as compared to earlier scans. In terms of an increased [18F]FDG uptake over time, dynamic micro positron emission tomography (microPET) delineated lymph node metastases and enabled metabolic examinations of the induced lung cancer metastases.ConclusionThe combination of contrast-enhanced microCT and dynamic microPET is feasible in rats for the visualization of mediastinal lymph node metastases.
Published Online: 2 September 2015
Gesehen am 11.02.2020